Impact of Varicocele Repair on Semen Parameters in Infertile Men: A Systematic Review and Meta-Analysis - Agarwal Ashok; Cannarella Rossella; Saleh Ramadan; Boitrelle Florence; Gül Murat; Toprak Tuncay; Salvio Gianmaria; Arafa Mohamed; Russo Giorgio I.; Harraz Ahmed M.; Singh Rajender; Garrido Nicolas; et al. (KOREAN SOC SEXUAL MEDICINE & ANDROLOGY, 2023)
Purpose:
Despite the significant role of varicocele in the pathogenesis of male infertility, the impact of varicocele repair (VR) on conventional semen parameters remains controversial. Only a few systematic reviews and meta-analyses (SRMAs) have evaluated the impact of VR on sperm concentration, total motility, and progressive motility, mostly using a before-after analytic approach. No SRMA to date has evaluated the change in conventional semen parameters after VR compared to untreated controls. This study aimed to evaluate the effect of VR on conventional semen parameters in infertile patients with clinical varicocele compared to untreated controls.
Materials and Methods:
A literature search was performed using Scopus, PubMed, Embase, and Cochrane databases following the Population Intervention Comparison Outcome (PICOS) model (Population: infertile patients with clinical varicocele; Intervention: VR [any technique]; Comparison: infertile patients with clinical varicocele that were untreated; Outcome: sperm concentration, sperm total count, progressive sperm motility, total sperm motility, sperm morphology, and semen volume; Study type: randomized controlled trials and observational studies).
Results:
A total of 1,632 abstracts were initially assessed for eligibility. Sixteen studies were finally included with a total of 2,420 infertile men with clinical varicocele (1,424 patients treated with VR vs. 996 untreated controls). The analysis showed significantly improved post-operative semen parameters in patients compared to controls with regards to sperm concentration (standardized mean difference [SMD] 1.739; 95% CI 1.129 to 2.349; p<0.001; I2=97.6%), total sperm count (SMD 1.894; 95% CI 0.566 to 3.222; p<0.05; I2=97.8%), progressive sperm motility (SMD 3.301; 95% CI 2.164 to 4.437; p<0.01; I2=98.5%), total sperm motility (SMD 0.887; 95% CI 0.036 to 1.738; p=0.04; I2=97.3%) and normal sperm morphology (SMD 1.673; 95% CI 0.876 to 2.470; p<0.05; I2=98.5%). All the outcomes showed a high inter-study heterogeneity, but the sensitivity analysis showed that no study was sensitive enough to change these results. Publication bias was present only in the analysis of the sperm concentration and progressive motility. No significant difference was found for the semen volume (SMD 0.313; 95% CI-0.242 to 0.868; I2=89.7%).
Conclusions:
This study provides a high level of evidence in favor of a positive effect of VR to improve conventional semen parameters in infertile men with clinical varicocele. To the best of our knowledge, this is the first SRMA to compare changes in conventional semen parameters after VR with changes in parameters of a control group over the same period. This is in contrast to other SRMAs which have compared semen parameters before and after VR, without reference to a control group. Our findings strengthen the available evidence and have a potential to upgrade professional societies' practice recommendations favoring VR to improve conventional semen parameters in infertile men.